Growth and economic performance of juvenile fat snook fed diets containing different protein levels - de Souza, José Humberto; Fracalossi, Débora Machado; Garcia, Alexandre Sachsida; Ribeiro, Flávio Furtado; Tsuzuki, Mônica Yumi (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this study was to evaluate the growth and economic performance of fat snook (Centropomus parallelus) fed six practical diets, containing different protein levels. Diets were formulated to contain the following protein levels: 375, 395, 416, 438, 473 and 490 g kg-1. Diets were offered until apparent satiation twice a day for 90 days. At the end of the experimental period, the body composition of the fish fed different diets did not differ significantly. The weight gain varied from 2.87±0.09 to 4.74±0.02 g from the lowest to the highest protein concentration. The protein concentration of 490 g kg-1 led to a decrease of 2.86±0.13 R$ kg-1 in the average feeding cost, an increase of 97.82±4.25% in the economic efficiency index, and a reduction of 102.91±4.58% in the cost index. The diet with the highest protein concentration and the energy/protein ratio of 7.27 Mcal kg-1 promotes the best economical and growth performances for juvenile fat snook.